Ethiopian Government scales up conservation agriculture-based sustainable intensification systems (CASI) via extension policy - CGIAR Research Program on Maize (2020)
The Ethiopian Ministry of Agriculture adopted CASI as part of its extension package, focused on maize-based systems, and cascaded it to regional agriculture bureaus for implementation in 2019.